Islami In Indonesia: An Introductory Remarks - M Machasin (Al-Jami'ah: Journal of Islamic Studies, 1992)
To speak about Islam in such a big population will involve a very large range of problems, from the insufficiency of the materials, to the disputes over subjects on which several researches have been done. The most important historicals are those related to its coming in this archipelago. To this day, no one can tell exactly when it came here for the first time, why it was accepted by the majority of the people, who propagated it here etc. The social scientist faces the problem that Islam is expressed here, as in any other part of Muslim world, in a vast number of variations. We can see, on the one hand, many "Muslims" in whom Islam. is only a "transparent veneer that fails to disguise the underlying substance of purely heathen character" On the other hand, we find puritans who see Islam as a total system that has to be applied in all aspects of their life. Therefore, we have to restrict ourselves to the most important subjects to talk about. As an introduction to the study of Islam in Indonesia, this paper will deal only with its system of beliefs and practices, its organizations, its educational institutions, its political appearances and its relations to the government Of course, these subjects cannot be dealt with sufficiently without placing them in its historical background.